Analysis of the Role of Homology Arms in Gene-Targeting Vectors in Human Cells - Ishii, Ayako; Kurosawa, Aya; Saito, Shinta; Adachi, Noritaka (PLOS ONE, 2014)
Random integration of targeting vectors into the genome is the primary obstacle in human somatic cell gene targeting. Non-homologous end-joining (NHEJ), a major pathway for repairing DNA double-strand breaks, is thought to be responsible for most random integration events; however, absence of DNA ligase IV (LIG4), the critical NHEJ ligase, does not significantly reduce random integration frequency of targeting vector in human cells, indicating robust integration events occurring via a LIG4-independent mechanism. To gain insights into the mechanism and robustness of LIG4-independent random integration, we employed various types of targeting vectors to examine their integration frequencies in LIG4-proficient and deficient human cell lines. We find that the integration frequency of targeting vector correlates well with the length of homology arms and with the amount of repetitive DNA sequences, especially SINEs, present in the arms. This correlation was prominent in LIG4-deficient cells, but was also seen in LIG4-proficient cells, thus providing evidence that LIG4-independent random integration occurs frequently even when NHEJ is functionally normal. Our results collectively suggest that random integration frequency of conventional targeting vectors is substantially influenced by homology arms, which typically harbor repetitive DNA sequences that serve to facilitate LIG4-independent random integration in human cells, regardless of the presence or absence of functional NHEJ.